2021
DOI: 10.1002/1878-0261.13082
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in the T cell receptor repertoire during treatment with radiotherapy combined with an immune checkpoint inhibitor

Abstract: Previous studies have indicated a synergistic effect between radiotherapy and immunotherapy. A better understanding of how this combination affects the immune system can help to clarify its role in the treatment of metastatic cancer. We performed T cell receptor (TCR) sequencing on 46 sequentially collected samples from 15 patients with stage IV non-small cell lung cancer, receiving stereotactic body radiotherapy combined with a programmed cell death ligand-1 (PD-L1) inhibitor. TCR repertoire diversity was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Archived biopsy samples were limited and sequencing of tumor‐infiltrating TCRs was unsuccessful. In a mouse tumor model, combined radiation therapy and ICB expanded the numbers of tumor‐reactive CD8 + T cells, leading to their infiltration at the tumor site 10 . Likewise, peripheral T cells expanded by the combination therapy recognized neoantigens, infiltrating the tumor sites in patients with NSCLC 8 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Archived biopsy samples were limited and sequencing of tumor‐infiltrating TCRs was unsuccessful. In a mouse tumor model, combined radiation therapy and ICB expanded the numbers of tumor‐reactive CD8 + T cells, leading to their infiltration at the tumor site 10 . Likewise, peripheral T cells expanded by the combination therapy recognized neoantigens, infiltrating the tumor sites in patients with NSCLC 8 .…”
Section: Resultsmentioning
confidence: 99%
“…In a mouse tumor model, combined radiation therapy and ICB expanded the numbers of tumor‐reactive CD8 + T cells, leading to their infiltration at the tumor site. 10 Likewise, peripheral T cells expanded by the combination therapy recognized neoantigens, infiltrating the tumor sites in patients with NSCLC. 8 Lussier et al recently reported that mutations elicited by radiation give rise to neoantigens presented by MHC molecules.…”
Section: Resultsmentioning
confidence: 99%
“…There are also several ICB-related factors to explore with next-generation sequencing that were not broached in these analyses. Relationships between circulating tumor cells [ 43 ], T cell receptor repertoires [ 44 ], and/or homologous recombination deficiency with ICB treatment have all been described [ 45 ], and further comparisons between stage III and IV TIMEs should consider these molecular characteristics. Regarding clinical characteristics, the data presented here are from pretreatment tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic changes to the TCR repertoire by RT were revealed by analyzing longitudinal peripheral blood samples, which showed increased frequencies of the top 10 TCR clonotypes post-RT, thus supporting the notion that radiation promotes peripheral expansion of tumor-resident T-cell clones. TCR sequencing was also performed in longitudinal blood samples from NSCLC patients receiving RT combined with anti-PD-L1 treatment; in this case, expansion of TCR clones was more frequent in treatment responders and was accompanied by a decreased TCR clonotype [ 80 ]. On the contrary, patients who clinically progressed after an initial response to therapy presented with increased TCR clonotype diversity [ 80 ].…”
Section: The Tcr Repertoire As a Biomarker For Rt-induced Systemic Im...mentioning
confidence: 99%
“…TCR sequencing was also performed in longitudinal blood samples from NSCLC patients receiving RT combined with anti-PD-L1 treatment; in this case, expansion of TCR clones was more frequent in treatment responders and was accompanied by a decreased TCR clonotype [ 80 ]. On the contrary, patients who clinically progressed after an initial response to therapy presented with increased TCR clonotype diversity [ 80 ]. These results demonstrate that RT may induce dynamic changes in the TCR repertoire via specific recognition of released tumor peptides from dying tumor cells resulting in systemic tumor responses.…”
Section: The Tcr Repertoire As a Biomarker For Rt-induced Systemic Im...mentioning
confidence: 99%